The Effect of Positioning, Product Quality, and Brand Image on Purchasing Decisions for Motor Vehicle Insurance at PT Asuransi Askrida Syariah, Medan Branch - Adisty Anggraini; Yenni Samri Juliati Nasution (Management Analysis Journal, 2023)
This study aims to determine the effect of positioning, product quality and brand image on the decision to purchase motor vehicle insurance at PT Asuransi Askrida Syariah Medan Branch. This study uses a causal association method and uses a quantitative approach. Data collection techniques in this study using a questionnaire. This study uses data analysis techniques; data validity and reliability tests, classical assumption tests, multiple regression analysis, and hypothesis testing. The population in this study are customers of PT Asuransi Askrida Syariah Cab. Medan, totaling 388 customers. Because the population is too much, more than 100, therefore the researchers took samples using the solvine formula. Therefore, the sample obtained was 80 customers. The research results show; positioning has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions, and brand image has a positive and significant effect on purchasing decisions.